Estrogen deficiency induces memory loss via altered hippocampal HB-EGF and autophagy. Issue 1 (January 2020) - Pandey, Rukmani; Shukla, Pallavi; Anjum, Baby; Gupta, Himanshu Pawankumar; Pal, Subhashis; Arjaria, Nidhi; Gupta, Keerti; Chattopadhyay, Naibedya; Sinha, Rohit A; Bandyopadhyay, Sanghamitra
Abstract : Estrogen deficiency reduces estrogen receptor-alpha (ERα) and promotes apoptosis in the hippocampus, inducing learning-memory deficits; however, underlying mechanisms remain less understood. Here, we explored the molecular mechanism in an ovariectomized (OVX) rat model, hypothesizing participation of autophagy and growth factor signaling that relate with apoptosis. We observed enhanced hippocampal autophagy in OVX rats, characterized by increased levels of autophagy proteins, presence of autophagosomes and inhibition of AKT-mTOR signaling. Investigating upstream effectors of reduced AKT-mTOR signaling revealed a decrease in hippocampal heparin-binding epidermal growth factor (HB-EGF) and p-EGFR. Moreover, 17β-estradiol and HB-EGF treatments restored hippocampal EGFR activation and alleviated downstream autophagy process and neuronal loss in OVX rats. In vitro studies using estrogen receptor (ERα)-silenced primary hippocampal neurons further corroborated the in vivo observations. Additionally, in vivo and in vitro studies suggested the participation of an attenuated hippocampal neuronal HB-EGF and enhanced autophagy in apoptosis of hippocampal neurons in estrogen- and ERα-deficient conditions. Subsequently, we found evidence of mitochondrial loss and mitophagy in hippocampal neurons of OVX rats and ERα-silenced cells. The ERα-silenced cells also showed a reduction in ATP production and an HB-EGF-mediated restoration. Finally in concordance with molecular studies, inhibition of autophagy and treatment with HB-EGF in OVX rats restored cognitive performances, assessed through Y-Maze and passive avoidance tasks. Overall, our study, for the first time, links neuronal HB-EGF/EGFR signaling and autophagy with ERα and memory performance, disrupted in estrogen-deficient condition.